2020
DOI: 10.1002/ajoc.202000334
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Cross‐Coupling Reactions for the Construction of Carbon‐Heteroatom Bonds

Abstract: Carbon-heteroatom bonds are ubiquitous among pesticides, pharmaceutical agents, and natural products. In recent years, significant progress has been made in transition-metal-catalyzed carbon-heteroatom bond formation. Especially, iron-catalyzed reactions have become a focused area in organic chemistry owing to their advantages of low cost, economical and environmental benignity. This review intends to summarize the recent advances in the construction of carbon-heteroatom bonds via cross-coupling reactions usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 202 publications
0
12
0
Order By: Relevance
“…In contrast to the well-established metal-catalyzed coupling reactions between aryl halides and phenols or aliphatic alcohols ( Scheme 1b ), 9 metal-catalyzed coupling reactions of aryl halides and allenols have not been developed ( Scheme 1c ). In a preliminary survey, the palladium- 10 and copper-catalyzed 11 coupling reactions between 4-iodoanisole and allenols were studied; however, only a trace amount of the desired allenyl aryl ether product was obtained ( Scheme 1c , for details, see the ESI ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the well-established metal-catalyzed coupling reactions between aryl halides and phenols or aliphatic alcohols ( Scheme 1b ), 9 metal-catalyzed coupling reactions of aryl halides and allenols have not been developed ( Scheme 1c ). In a preliminary survey, the palladium- 10 and copper-catalyzed 11 coupling reactions between 4-iodoanisole and allenols were studied; however, only a trace amount of the desired allenyl aryl ether product was obtained ( Scheme 1c , for details, see the ESI ).…”
Section: Resultsmentioning
confidence: 99%
“…Another earth abundant, low-cost transition metal with low toxicity, which can be utilized as catalyst in C-S cross-couplings is iron. 64 The first iron catalyzed Migita type coupling was published by Bolm and co-workers in 2008 (Scheme 19). 65 Aryl iodides and (hetero)aryl thiols were coupled with FeCl3 as lowcost precatalyst and DMEDA (L8, N,N'-dimethylethylenediamine) as bidentate amine ligand at high temperatures.…”
Section: Ironmentioning
confidence: 99%
“…Transition-metal-catalyzed cross-coupling reactions have been found broad applications for the construction of carbon-carbon and carbon-heteroatom bonds enable the facile preparation of more complex molecules ( Miyaura, 2002 ; Magano and Dunetz, 2011 ; Negishi, 2011 ; Suzuki, 2011 ; Guo and Rueping, 2018 ; Zhang et al, 2020 ). In 1972, Kumada and Tamao ( Tamao et al, 1972 ) reported the cross-coupling reaction of Grignard reagents (RMgX) with organic halides (R’X) catalyzed by nickel/phosphine system.…”
Section: Introductionmentioning
confidence: 99%